Thème, histoire et problématique en éducation à la sécurité routière - Line Courteaud; Christian Roux (Université de Provence, 2013)
With the development of techniques and technologies applied to the automobile, the road environment became a complex area in which the regulation legislation and driving license prove insufficient to ensure the safety of all road users. Would driver's training more in line with the complexity of the road system? Research was conducted at European level, in order to analyze the effects of the driver on the behavior and abilities training systems (and their limits) opportunities. In light of this research, the self-evaluative capacity was selected as a dynamic change in the attitudes and behavior of the driver.